Aplicación de un modelo de análisis de ciclo de vida para evaluación de paneles prefabricados. - Molina Muñoz, Edna Soledad (2025)
The evaluation of prefabricated panels using a Life Cycle Assessment (LCA) model is a comprehensive approach that helps understand and improve their environmental impact—from the extraction of raw materials to final disposal. LCA has become an essential tool in sustainable construction, offering a holistic view of the environmental impacts associated with the production and use of building materials. The main objective of this study is to apply a life cycle assessment model to evaluate prefabricated panels. These panels are widely used in construction due to their advantages, including faster construction, controlled quality, and reduced on-site waste. Prefabricated panels can be made from various materials, including concrete, wood, and plastic composites. The prefabrication process enables the production of standardized components in a controlled environment, reducing variability and enhancing installation accuracy. Therefore, life cycle analysis is a valuable tool for assessing the environmental performance of prefabricated panels and guiding decisions toward more sustainable practices in the construction industry. Through LCA, we can identify the most critical stages with respect to environmental impact and develop strategies to enhance the sustainability of these products based on the evaluated impacts throughout their life cycles. This analysis methodology adheres to ISO 14044:2006 standards. Keywords: Life cycle, Prefabricated panels, Environmental impact, Sustainability.